A fan effect in anaphor processing: effects of multiple distractors - Autry, Kevin S.; Levine, William H. (Frontiers in Psychology, 2014)
Research suggests that the presence of a non-referent from the same category as the referent interferes with anaphor resolution. In five experiments, the hypothesis that multiple non-referents would produce a cumulative interference effect (i.e., a fan effect) was examined. This hypothesis was supported in Experiments 1a and 1b, with subjects being less accurate and slower to recognize referents (1a) and non-referents (1b) as the number of potential referents increased from two to five. Surprisingly, the number of potential referents led to a decrease in anaphor reading times. The results of Experiments 2a and 2b replicated the probe-recognition results in a completely within-subjects design and ruled out the possibility that a speeded-reading strategy led to the fan-effect findings. The results of Experiment 3 provided evidence that subjects were resolving the anaphors. These results suggest that multiple non-referents do produce a cumulative interference effect; however, additional research is necessary to explore the effect on anaphor reading times.